1‐(Methylamino)anthracene – An Accessible Building Block for Photoresponsive Compounds. Issue 47 (16th November 2018) - Ulatowski, Filip; Melaniuk, Karolina
Abstract : In this paper we present a convenient and scalable synthesis of 1‐(methylamino)anthracene, which is a potent building block for the construction of photoresponsive materials. With this structural motif we have synthesized an anion receptor bearing two anthracene groups. Interaction of a chloride anion with the anthracene moieties increases the association constant. Photocycloaddition allows to obtain a single macrocyclic receptor, which exhibits higher binding constants due to the macrocyclic effect. Abstract : Facile synthesis provides a novel anthracene‐based amine, which acts as a versatile building block for the construction of photoswitchable receptors. Incorporation of this structural motif into dipicolinic amide provides a photoresponsive anion receptor. Upon irradiation with 360 nm light, cycloaddition occurs to yield macrocyclic receptors with higher affinities for anions.